Global Program for Avian Influenza Control and Human Pandemic Preparedness and Response : Project Accomplishments - Jonas, Olga; Warford, Lucas (World Bank Group, Washington, DC, 2015)
This report reviews some of the accomplishments of the Global Program for Avian Influenza Control and Human Pandemic Preparedness and Response (GPAI). This multisectoral program comprised 72 projects in 60 developing countries in all regions and received $1.3 billion in financing from the World Bank. This support for GPAI projects was one of the World Bank s contributions to a coordinated global response to the threats of avian and pandemic influenzas, which benefited from financing of $4 billion from 35 donors in 2006-2013. Thanks to this support, developing countries strengthened their capacity for early and effective disease control, bringing substantial public health and economic benefits to the countries and to the world. According to Harvard University Professor and former US Treasury Secretary Lawrence Summers, "[veterinary and human public health systems are] probably the single most important area for productive investment on behalf of mankind." Indeed, circulation of the highly pathogenic avian flu virus was reduced, helping to lessen the likelihood of onset of a pandemic. Moreover, the projects improved public health systems for reducing locally-relevant health threats. The report presents a brief background on the global program and cross-country accomplishments and then highlights accomplishments for each project, by region.